PRESTIGIOUS UNIVERSITIES IN THE DIGITAL SPACEANALYSIS OF MANAGEMENT AND REPUTATION OF STUDENTSINFLUENCE ON CHOICE (Journal of Media studies, 2023)
Reputation management is one of the important factorsinfluencing the development of an organization, including for universities.However, today, when the digital world is rapidly expanding and begins tooccupy almost the main place in building a positive reputation, it is necessary toplace considerable emphasis on maintaining an image in the Internet space.Therefore, the purpose of this article is to study how the university shouldmaintain its reputation in the digital environment, taking into account theinterests and preferences of future students. Because in the conditions of growingcompetition in the higher education environment, it is necessary to clearly builda marketing strategy in order to create a favorable image and recruit the beststudents. The study showed that 55% of prospective students spend almost 5hours online every day. They spend more time on social networks, namelyInstagram, TikTok and want to receive information through the same sources. Itwas also revealed that mostly 11th grade students, before choosing universities,visit their websites and draw conclusions. Based on the results of the research,the university needs to introduce and develop social networks in most aspects ofits activities and simultaneously improve and simplify its websites.